Improve Work-Life Balance Through Optimizing Employee Spirituality - Yarsi, Marna Rita; Thoyib, Armanu; ., Rofiaty; Irawanto, Dodi Wirawan (Journal of Ecohumanism, 2025)
Adaptation during the Covid-19 pandemic has caused work patterns and lifestyle changes. Technological developments make it possible for someone to be very accessible anytime, anywhere, so the boundaries between work life and personal life are increasingly biased. This research aims to test 4 (four) hypotheses about whether Work-Life Balance (WLB) is influenced by Emotional Intelligence (EI) and Employee Spirituality (ES) either directly or through EI as a mediating variable and whether ES influences EI. This research sampled 439 Sharia bank employees in DKI Jakarta at the manager, officer, and staff levels. The data collection method uses a questionnaire with a Likert Scale, which is processed and analyzed using PLS-SEM (Partial Least Square-Structural Equation Modeling). The results show that ES has a significant positive effect on WLB, ES has a significant positive impact on EI, EI has a significant negative effect on WLB, and EI mediates the negative effect of ES on WLB. The results of this study need to be further tested on different research objects to be generalized, whether the significant negative influence of EI on WLB can occur in research objects with different organizational backgrounds and environmental conditions. Further research is needed using different instruments to measure the influence of EI on WLB. The study's limitations also lie in the data collection technique, which is only carried out through questionnaires; no further in-depth interviews are carried out to confirm the answers to the questionnaire items, especially in sentences that have negative meanings in measuring and reflecting WLB.